Meningkatkan Kemampuan Guru Dalam Mendidik Karakter Siswa Berbasis Keunggulan Budaya Lokal - Badeni, Badeni; Saparahayuningsih, Sri; Juarsa, Osa (Perkumpulan Dosen Muda Bengkulu, 2024)
This community service project intends to increase the abilities of instructors at State Junior High School 19 Bengkulu City to instill ethical principles and character in their students via exposure to local cultural excellence. Community service activities are carried out using a mix of lecture methods, talks, workshops (in the form of Forum Group Discussion (FGD)), simulations / practices, role playing, and panel group discussions. Implementing community service activities using a combination of these methods has improved the ability of 19 Junior High School teachers in (1) mastering the concepts / theories of ethical value education (inculcation approach, cognitive moral development approach, values analysis approach, values clarification approach, action learning approach, and value integrated approach); (2) identify character values of local cultural excellence that are consistent with the character values in the teaching materials to be taught to students in accordance with core competencies, basic competencies, and indocators; (3) analyze subjects, core competencies, basic competencies, grades, and indicators per grade level; and (4) conduct an analysis based on core competencies, basic competencies, indicators, and values of local cultural excellence that will be educated to students.Â